Institutional directors and board compensation: Spanish evidence - Felix J. López Iturriaga; Emma García-Meca; Fernando Tejerina-Gaite (BRQ Business Research Quarterly, 2015)
We address the influence of directors who represent institutional investors in three aspects of board compensation policies: level of compensation, composition, and performance sensitivity. We differentiate pressure-sensitive directors (i.e., with business links) and pressure-resistant directors (i.e., without business links). Our results show that pressure-resistant directors decrease total board compensation and its fixed proportion, whereas they increase the variable proportion of total remuneration and the pay-for-performance sensitivity. By contrast, pressure-sensitive directors offer the opposite results. These findings are consistent with the view that institutional investors are not a homogeneous group and that pressure-resistant directors fulfill a more thorough monitoring role."
Keywords: 650; Corporate governance; Institutional investors; Board of directors; Remuneration; Compensation